Achieving high coverage in Rwanda's national human papillomavirus vaccination programme - Agnes Binagwaho; Claire M Wagner; Maurice Gatera; Corine Karema; Cameron T Nutt; Fidele Ngabo (The World Health Organization, 2012)
PROBLEM: Virtually all women who have cervical cancer are infected with the human papillomavirus (HPV). Of the 275 000 women who die from cervical cancer every year, 88% live in developing countries. Two vaccines against the HPV have been approved. However, vaccine implementation in low-income countries tends to lag behind implementation in high-income countries by 15 to 20 years. APPROACH: In 2011, Rwanda's Ministry of Health partnered with Merck to offer the Gardasil HPV vaccine to all girls of appropriate age. The Ministry formed a "public-private community partnership" to ensure effective and equitable delivery. LOCAL SETTING: Thanks to a strong national focus on health systems strengthening, more than 90% of all Rwandan infants aged 12-23 months receive all basic immunizations recommended by the World Health Organization. RELEVANT CHANGES: In 2011, Rwanda's HPV vaccination programme achieved 93.23% coverage after the first three-dose course of vaccination among girls in grade six. This was made possible through school-based vaccination and community involvement in identifying girls absent from or not enrolled in school. A nationwide sensitization campaign preceded delivery of the first dose. LESSONS LEARNT: Through a series of innovative partnerships, Rwanda reduced the historical two-decade gap in vaccine introduction between high- and low-income countries to just five years. High coverage rates were achieved due to a delivery strategy that built on Rwanda's strong vaccination system and human resources framework. Following the GAVI Alliance's decision to begin financing HPV vaccination, Rwanda's example should motivate other countries to explore universal HPV vaccine coverage, although implementation must be tailored to the local context.